Single stage versus two-stage orthoplastic management of bone infection. Issue 3 (March 2022) - Nasser, Ahmed A.H.; Fenton, Paul; Bose, Deepa
Highlights: The single-stage orthoplastic approach to bone infection produces comparable results to a two-stage procedure. The risk of amputation does not differ between the single stage and two-stage approach. Time to bony union in open fracture related infections is longer when compared to closed injuries. Abstract: Introduction: Bone infection cases with major soft tissue loss have conventionally been treated with a staged orthoplastic approach, addressing the infection first followed by definitive management to achieve bony stability and soft tissue cover. In the last few decades, specialist centers have advocated for single stage bony stabilization with soft tissue coverage. We aimed to investigate the outcomes of patients that underwent a single stage versus a two-stage orthoplastic intervention. Methods: Using an existing 2009–2019 database from a single major trauma centre, we identified all adults with a diagnosis of fracture related infection (FRI) or osteomyelitis (OM). The primary outcome was resolution of infection. Secondary outcomes included time to bony union, amputation, failure of orthopaedic fixation, mortality, and return to theatre. Results: A total of 96 patients were included. 71 patients (74%) underwent a single stage procedure; out of which 61 were FRI. 25 patients (26%) underwent a two-stage procedure; out of which 24 were FRI. The average follow up for the single stage and two-stage cohorts was 32.1 and 30.3 months, respectively. Resolution of infection without the need for an amputation was achieved in 67 (94.4%) patients in the single stage cohort and in 23 (92%) patients in the two-stage cohort. When compared to the two-stage group, the single stage cohort had less recurrence of infection (9.9% versus 12%, p  = 0.72), lower rates of amputation (8.5% versus 12%, p  = 0.69), lower rates of failure of orthopaedic fixation (11.1% versus 13%, p  = 0.82), but higher average time to bony union (15.25 months versus 12.35, p  = 0.42). The differences were not statistically significant. A total of 37 patients (52.1%) had an unplanned return to theatre in the single stage compared to 12 (48%) in the two-stage cohort. In subgroup analysis of FRI cases, open fractures had a longer time to bony union when compared to closed fractures (19.7 versus 11.6 months, p  = 0.01). No mortality was observed in both cohorts. Conclusions: The single stage orthoplastic approach to bone infection is effective if planned carefully with clinical outcomes comparable to the two-stage approach. Further research should examine factors associated with unplanned return to theatre and any variation in treatment of bone infection across regions.